Symptomatic marginal ulcer after pancreatoduodenectomy - Sulieman, Ibnouf; Strobel, Oliver; Mihaljevic, André Leopold; Müller, Beat P.; Diener, Markus K.; Mehrabi, Arianeb; Schneider, Martin; Berchtold, Christoph; Tjaden, Christin; Hinz, Ulf; Feißt, Manuel; Büchler, Markus W.; et al. (Surgery, 2020)
Background - Marginal ulcer is a well-known complication after pancreatoduodenectomy. In light of increasing long-term survival after pancreatoduodenectomy, the identification of risk factors and preventive strategies are of utmost importance. We assessed the incidence, clinical impact, and potential risk factors of marginal ulcer after pancreatoduodenectomy. - Methods - A prospectively maintained database of patients undergoing pancreatoduodenectomy was analyzed retrospectively. Univariate and bivariate competing-risk Cox regression analyses were performed to identify risk factors for marginal ulcer. - Results - Two hundred and fifty-five consecutive patients underwent pancreatoduodenectomy. The median follow-up was 35.7 months. Marginal ulcer was diagnosed in 19 patients (7.5%), and the median time from pancreatoduodenectomy to marginal ulcer diagnosis was 450 days. Thirteen of these 19 patients presented with abdominal pain, melena, or anemia. In all these 13 patients, marginal ulcer resolved with proton pump inhibitor therapy and endoscopic surveillance. Six patients with marginal ulcer presented with an acute abdomen and underwent emergency laparotomy for marginal ulcer perforation and peritonitis. There was no marginal ulcer-related mortality. Univariate and bivariate competing-risk analyses showed an increased risk for marginal ulcer with discontinuation of proton pump inhibitor therapy, smoking, alcohol intake, and the use of non-steroidal anti-inflammatory drugs. Discontinuation of proton pump inhibitor therapy was an independent risk factor for marginal ulcer development. - Conclusion - Marginal ulcer is a relevant long-term complication after pancreatoduodenectomy that occurs more frequently after proton pump inhibitor therapy is discontinued. Based on our data, permanent use of proton pump inhibitor after pancreatoduodenectomy is strongly recommended especially for those patients who smoke, consume alcohol, or use non-steroidal anti-inflammatory drugs.